Center of Rotation and Hysteresis Quantification in the Wrist Utilizing Four-Dimensional Computed Tomography - Norman, Elizabeth; Robinson, Sydney; Chambers, Spencer; Rainbow, Michael; Suh, Nina; Lalone, Emily (Journal of Wrist Surgery, 2025)
Background Wrist injuries limit function and can lead to long-term pain and disability. Current interventions aim to decrease pain and restore healthy function; however, healthy function during dynamic motion has not been fully characterized. Four-dimensional computed tomography (4DCT) can capture dynamic bony motion providing new insight to the dynamic wrist joint.Materials and Methods Ten young healthy participants were scanned using a 4DCT scanner and three-dimensional (3D) models were made of the radius and carpal bones. Using helical axes and local coordinate systems for the radius, rotations of each bone were measured, and center of rotation was determined. In addition, hysteresis was quantified by measuring hysteresis area, the area between the curves of the forward and reverse motion of the wrist joint.Results The results showed that the wrist axis of rotation was located more proximal (−15.2 ± 1.3 mm distal) and dorsal (−0.8 ± 2.6 mm dorsal) in extension as compared with the flexion positions (−20.4 ± 1.6 mm distal; 3.9 ± 2.5 mm volar). In addition, no statistical differences were identified between the different directions of motion at each angle of wrist motion, with the exception of the trapezium at 30 degrees of extension. The largest hysteresis effect was noted in the trapezoid (112.8 deg2) and the smallest effect identified in the lunate (46.0 deg2).Conclusion The results of this study may provide a better understanding of the dynamic nature of the wrist joint for identification of ligamentous injuries and replication of joint motion after surgical intervention.
Keywords: wrist; hysteresis; center of rotation; 4DCT; kinematics